Representasi Ageisme dan Ageing dalam Film Mahasiswi Baru Karya Monthy Tiwa - Syafira Aulia Arsani (Jurnal Ilmu Komunikasi, 2022)
People entering the final stages of life or old age (old age) are often labeled with negative stereotypes regarding physical, psychological and social changes. Various depictions of the self-image of the elderly appear in various texts. This article discusses the self-image of the elderly in the text of a film entitled “New Student by using Roland Barthes' semiotic theory in the form of the natural meaning of a scene in a film consisting of denotation, connotation and myth. With this the researcher analyzes the representation or image of the elderly that is constructed individually. From the results of an in-depth and thorough analysis of the observations of the scenes in the film, it can be concluded that the positive image of the elderly is built by looking for loopholes. It has weaknesses, strengths, and positive images. The depiction of negative images is not eliminated.